Population dynamics of the Magpie "Pica pica" in Zielona Góra - Burda, Ewa (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The study describes the development of the population of Magpies "Pica pica" in the city of Zielona Gora, western Poland, based on earlier reports and a recent count in 2016. In the first half of the 20th century, there were only 5-7 pairs, corresponding to a density of 1.4 pairs/km2. At that time 2-3 pairs nested in the city center.
Keywords: Magpie; Pica pica; synurbization; urbanized; population dynamics; urban habitat preferences; nesting trees; Zielona Góra